COVID-19 pandemic: Nigerians’ perception about the National health system and socio-political rights - Dada, Samuel Oluwasogo; Oniya, Olawale Ayomikun; Hussain, Oluwatobi James (International Journal of Research in Medical Sciences, 2020)
Background: The study investigated the knowledge of Nigerian youths on COVID-19 and their perception about COVID-19, National health system and socio-political right. Methods: A descriptive study designed was adopted using an online survey method. Google form was used to elicit responses from 225 Nigerian youths across the six geo-political zones of Nigeria. A 12-point knowledge scale was used to assess knowledge, while a 12-point perception scale was used to determine respondents’ perception. Descriptive statistics was used for data analysis. Results: The respondents’ mean age was 28.2±6.1 years. Majority (58.0%) were from the Southern part of Nigeria while 42.0% were from the Northern part of Nigeria. Also, 63.0% of the respondents had at least a first degree and majority (60.4%) were female. Almost all (87.2%) the respondent had good knowledge on the novel COVID-19, with mean knowledge score of 9.5±2.6. About one-third (31.6%) of the respondent reported the Nigeria health system is too weak and they desired to leave the country, 84.9% believed the federal Government of Nigeria is not doing enough in handling the COVID-19 and 45.5% felt Nigeria is not a safe place during a pandemic. Conclusions: The general perception of Nigerian’s youth about the health system and Government handling of the COVID-19 was poor. A good knowledge of COVID-19 was documented. There is therefore the need for Government to scale up and strengthen the health system capacity to handle health emergencies such as the COVID-19.